The Effect of Rhizobium japonicum on the Growth of Soybean Cultivars in Coastal Area - Okti Purwaningsih; C. Tri Kusumastuti; Y. Sulistyo Nugroho; Casper Yoda Morib (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2019)
The natural resources of the coastal area in Indonesia have the potential to be developed as an agricultural land with the support of both cultivation technology and land processing, which one of them was done by using Rhizobium japonicum bacteria to meet the need of nitrogen in the soybean plants. This study aimed to determine the characteristics of nitrogen fixation in various soybean cultivars planted in the coastal area. The research was conducted in Mancingan, Parangtritis, Kretek, Bantul, DIY. The study was designed in Completely Randomized Design which consisted of two factors and was repeated three times. Factor I was Rhizobium japonicum inoculation (with inoculation and without inoculation); factor II was 10 various cultivars of soybean (Grobogan, Burangrang, Argomulyo, Anjasmara, Dena 1, Gema, Kaba, Wilis, Sinabung, Gepak Kuning). The results showed that the inoculation of Rhizobium japonicum in soybean cultivars in a coastal area could increase the number of root nodule, dry weight of root nodule, dry seed weight per plant, and harvest index. Burangrang cultivar planted in the coastal area was the most responsive to Rhizobium japonicum inoculation among other soybean cultivars tested.